Discrepancies between clinical diagnoses and autopsy findings - Coradazzi, A.L.; Morganti, A.L.C.; Montenegro, M.R.G. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2003)
Autopsy examination is considered to be an essential element for medical auditing and teaching. Despite the significant progress in diagnostic procedures, autopsy has not always confirmed the clinical diagnosis. In the present study, we compared the diagnosis recorded on medical charts with reports of 96 autopsies performed at the University Teaching Hospital of the Faculdade de Medicina de Botucatu, Botucatu, SP, Brazil, between 1975 and 1982, and of 156 autopsies performed at the same institution between 1992 and 1996. The clinical diagnosis of the basic cause of death was confirmed at autopsy in 77% of cases. The percent confirmation fell to 60% when the immediate terminal cause of death was considered, and in 25% of cases, the terminal cause was only diagnosed at autopsy. The discrepancies between clinical and autopsy diagnosis were even larger for secondary diagnoses: 50% of them were not suspected upon clinical diagnosis. Among them, we emphasize the diagnosis of venous thromboses (83%), pulmonary embolisms (80%), bronchopneumonias (46%) and neoplasias (38%). Iatrogenic injuries were very frequent, and approximately 90% of them were not described in clinical reports. Our results suggest that highly sensitive and specific diagnostic tests are necessary but cannot substitute the clinical practice for the elaboration of correct diagnoses.
Keywords: Autopsy diagnosis; Clinical diagnosis; Iatrogenic injuries